Implementation of the Principle of Divinity in the Spirit of Mutual Cooperation in the Organization of Student Associations Majoring in Mechanical Engineering at Medan State University as a Form of Religious Moderation. To Strengthen Religious Harmony Rel - Silfani, Dwi; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Naibaho, Angelina Rolas; Batubara, Radja Marihat; Ariza, Dafa (Peneliti.net, 2023)
The importance of implementing the principle of divinity in the spirit of gotong royong as a form of religious moderation in order to strengthen religious harmony in Indonesia. This reflects the challenges of religious harmony in the midst of religious diversity in Indonesia. The research method applied in this study involves the use of questionnaires distributed to members of the Mechanical Engineering Department Student Association at Medan State University as many as 15 respondents. This approach is designed to collect relevant data and this study aims to analyze the correlation between the level of understanding of the principle of divinity and the effectiveness of its implementation in the spirit of gotong royong, as well as its impact on religious harmony within the Medan State University at the Mechanical Engineering Department Student Association